The Influence of transformational Leadership of School Principals, Teacher Compensation, and School Organizational Climate on Kindergarten Teachers’ Performance - Nantiyem; Ysh, A.Y Soegeng; Bunyamin (IQRO: Journal of Islamic Education, 2024)
This study examines the impact of transformational leadership, teacher compensation, and school organizational climate on kindergarten teacher performance in Temanggung Regency. Using a quantitative approach and survey method, data were collected from 146 teachers across three districts and analyzed with descriptive statistics and multiple linear regression. The results show that transformational leadership contributes 21.0%, teacher compensation 35.3%, and school organizational climate 37.2% to teacher performance. Together, these factors explain 55.4% of the variance in performance. The findings suggest that improving principal leadership quality, increasing teacher compensation, and enhancing the school climate are crucial to boosting teacher performance. It is recommended that the local education office focus on strengthening these areas to improve teacher performance in Temanggung Regency. Keywords: : Transformational leadership; teacher compensation; organizational climate; kindergarten teacher performance.